Screening of Actinomycetes Producing an ATPase Inhibitor of Japanese Encephalitis Virus RNA Helicase from Soil and Leaf Litter Samples - SHANTI RATNAKOMALA; RONI RIDWAN; PUSPITA LISDIYANTI; . ABINAWANTO; UTAMA ANDI (Indonesian Society for microbiology, 2011)
Actinomycetes are commercially important microorganisms for the production of antibiotics, enzymes, inhibitors of enzymes, and other bioactive secondary metabolites. Some 853 isolates of actinomycetes were isolated from soil and leaf litter samples in Kupang NTT and Enrekang, South Sulawesi. Those isolates were then tested for inhibition of ATPase activity of RNA helicase from Japanese encephalitis virus (JEV), in order to identify a drug candidate for the treatment of JEV infection. Results revealed that 14 isolates have relatively high inhibition-activity on JEV ATPase activity of the JEV-RNA-helicase, which range from approximately 40.0-50.0% inhibition. The highest inhibition-activity was identified in Actinoplanes philippinensis 5-849 with 49. 9% of inhibition-activity and Streptomyces chartreusis 5-095 with 49.2% of inhibition-activity